New economy - Boothby, Robert (London, 1943)
The central theme of this book is monetary policy. I hope the reader will not be discouraged on that account. The subject is not in itself complicated or difficult. It has been made so by those who have deliberately sought to cloud the issues, and to use a favourite expression of Mr. Churchill's-darken counsel. Real wealth consists of goods and services, and is produced by manpower, materials, and machinery. Money is simply a convenient medium for exchanging these goods and services, and for measuring their value. It is, of course, highly in convenient when the measuring-rod itself begins to vary. No grocer would expect to earn his living if someone came into his shop every night and loaded his weights. Yet that is what the bankers did to the basic producers of this country, and ultimately of the world, for years.
Keywords: Economic policy